Selection of emission factor standards for estimating emissions from diesel construction equipment in building construction in the Australian context. (1st February 2017) - Zhang, Guomin; Sandanayake, Malindu; Setunge, Sujeeva; Li, Chunqing; Fang, Jun
Abstract: Emissions from equipment usage and transportation at the construction stage are classified as the direct emissions which include both greenhouse gas (GHG) and non-GHG emissions due to partial combustion of fuel. Unavailability of a reliable and complete inventory restricts an accurate emission evaluation on construction work. The study attempts to review emission factor standards readily available worldwide for estimating emissions from construction equipment. Emission factors published by United States Environmental Protection Agency (US EPA), Australian National Greenhouse Accounts (AUS NGA), Intergovernmental Panel on Climate Change (IPCC) and European Environmental Agency (EEA) are critically reviewed to identify their strengths and weaknesses. A selection process based on the availability and applicability is then developed to help identify the most suitable emission factor standards for estimating emissions from construction equipment in the Australian context. A case study indicates that a fuel based emission factor is more suitable for GHG emission estimation and a time based emission factor is more appropriate for estimation of non-GHG emissions. However, the selection of emission factor standards also depends on factors like the place of analysis (country of origin), data availability and the scope of analysis. Therefore, suitable modifications and assumptions should be incorporated in order to represent these factors. Highlights: A comprehensive review of emission factor standards for estimating emissions from construction equipment is presented. A fuel based emission factor is more suitable for estimation of GHG emissions. A time based emission factor is more suitable for estimation of non-GHG emissions. A selection process is developed to identify the most suitable emission factor standards for construction work in Australia.